A meta-ethnographic systematic review of women’s experiences of homelessness in high income environments - Radcliffe, Maxine; Cronin, Anne; Stokes, Diarmuid; Douma, Matthew J.; Jackson, Debra; Kroll, Thilo; Frazer, Kate (PLOS ONE, 2026)
Background Homelessness is a significant public policy and health service challenge globally. Often identified as a ‘wicked problem’ homelessness is hard to define with limited data confirming the exact numbers of people who are homeless due to varying metrics employed many of which likely exclude women by design. Research and policy have primarily focused on the experiences of single men, and the impact of homelessness on women and their experiences of it are not well understood. Objective To synthesise evidence from qualitative studies of homelessness to identify key dimensions of women in high-income countries (HIC) and their experiences navigating lives when homeless. Methods Systematic searches of six databases [MEDLINE, Embase, Global Health, PsycINFO, CINAHL and ASSIA] were completed from 2012 to 8th January 2024. We included peer-reviewed publications published in English reporting primary qualitative data on women’s experiences of homelessness in high-income countries only. A review protocol was developed and published. Noblit and Hare’s Metaethnography steps guided the synthesis and are reported according to the eMERGe guidelines. Findings Thirty-two studies were identified describing the experiences of 227 women across nine HICs. A conceptual model comprising three themes is presented within a social-ecological theoretical framework within structural and temporal axes of impact with effects on individual and societal levels. These themes, 1) Precarity, 2) Existing with Risk and Surviving, and 3) Fracturing Identity, describe the implications of homelessness and how the experience of precarity impacts identity and decision-making abilities. The impact of risk arising from violence and exclusion, coupled with descriptions of shame and stigma, presents insight into women’s experiences that have hitherto had a limited presence in clinical discourses. Conclusions The evidence in this review highlights the perpetual reporting of a deficit lens on homelessness. Women experiencing homelessness in HICs are a heterogeneous group that is poorly recognised and understood in the literature. It appears that there is a lack of tailored and responsive service availability and that this further perpetuates the structural underpinnings of homelessness, which cluster in highly gendered ways.